Determination of fourteen UV filters in bathing water by headspace solid-phase microextraction and gas chromatography-tandem mass spectrometry. Issue 39 (13th September 2016) - Vila, Marlene; Celeiro, Maria; Lamas, J. Pablo; Dagnac, Thierry; Llompart, Maria; Garcia-Jares, Carmen
Abstract : A headspace SPME-GC-MS/MS method for the analysis of 14 UV filters in different types of bathing water samples has been developed. Abstract : A methodology based on solid-phase-microextraction (SPME) followed by gas chromatography-tandem mass spectrometry (GC-MS/MS) has been developed for the simultaneous analysis of 14 UV filters of different chemical nature in water. The extraction parameters (the extraction mode and temperature, the fibre coating, and the addition of salt) were optimised by means of experimental designs in order to select the best extraction conditions. The final proposed conditions were 10 mL of water sample with 35% NaCl added, extracted in the headspace mode with a polyacrylate (PA) fibre at 100 °C for 20 minutes. The SPME-GC-MS/MS method was validated in terms of linearity ( R 2 ≥ 0.9937), accuracy and precision, obtaining LODs in the range of 0.068–12 ng L −1 . The validated methodology was then applied to the analysis of different bathing water samples including sea, river, spa, swimming pool, and aquapark water, allowing the detection of 10 of the 14 target compounds; some of them were found at concentrations up to 692 ng mL −1 .